Role of physical processes in determining the nature of fisheries in the eastern Arabian Sea. (March 2019) - Shankar, D.; Remya, R.; Anil, A.C.; Vijith, V.
Highlights: Impact of physics on fisheries in the eastern Arabian Sea. Longer growing season, small phytoplankton imply carnivorous fishery in the north. Shorter growing season, large phytoplankton imply planktivorous fishery in the south. Weaker upwelling in the centre implies weaker fishery compared to south. Physical forcing linked to decline in sardine catch from south to centre. Abstract: We use available data and model simulations to make a case for physical forcing of the spatial variation in the nature of fisheries off the west coast of India in the eastern Arabian Sea (EAS). The approach is heuristic, but builds the case on the basis of model simulations and well-established implications of specific physical processes for the marine ecosystem. We address three questions. First, we show that it is differences in the physical forcing lead to a carnivore-dominated fishery in the northeastern Arabian Sea (NEAS) and a planktivore-dominated fishery in the southeastern Arabian Sea (SEAS). In the NEAS, the growing season for phytoplankton is longer because the upwelling during the summer monsoon (June–September) is followed by convective mixing during the winter (November–February) monsoon. Detrainment, again leading to a phytoplankton bloom, follows the convective-mixing season. The long duration of the growing season permits the existence of a longer food chain, leading to a carnivore-dominated fishery. In the NEAS, the phytoplankton also tend to be small owing to weaker upwelling during the summer monsoon and limitations imposed by silicates, turbulence, and light during the winter monsoon. In the SEAS, the stronger upwelling implies larger phytoplankton that can be directly fed on by fish like the oil sardine. The growing season in the SEAS is also limited to the summer monsoon, predisposing the ecosystem towards a shorter food chain. Second, we show that it is the differences in physical forcing that lead to the weaker fishery in the central-eastern Arabian Sea (CEAS) compared to the SEAS. Though the growing season in both SEAS and CEAS is comparable, the upwelling is weaker in the CEAS, implying a limitation of nitrate and a dominance of small phytoplankton in contrast to the SEAS, where large phytoplankton dominate. Hence, the phytoplankton biomass is less in the CEAS compared to the SEAS and the region cannot support a fishery comparable to the SEAS. Third, we show that it is the difference in physical forcing that leads to a sharp decline in the catch of oil sardines from the SEAS to the CEAS even as the catch of mackerel does not change much. Not only does the stronger upwelling in the SEAS compared to the CEAS imply a larger size of the phytoplankton in the former, but the phytoplankton biomass is also higher in the SEAS. The zooplankton standing stock, as estimated using the backscatter measured by the acoustic Doppler current profilers (ADCPs) deployed on moorings, is determined more by the vertical movement of the depth of the 20 °C isotherm (D20). Hence, the standing stock of zooplankton tends to be lowest when upwelling peaks, i.e., during the summer monsoon. This is also the time when the phytoplankton biomass peaks. The phytoplankton surplus is greater in the SEAS compared to the CEAS because of the stronger upwelling, which implies higher primary productivity and a shallower D20, in the SEAS. This phytoplankton surplus can be fed on by the oil sardine, which prefers diatoms. In contrast, the higher zooplankton standing stock in the CEAS competes with the oil sardine off Karnataka and Goa, where the mackerel, which feed on zooplankton, is the dominant fishery. The weaker upwelling implies lower primary productivity and a deeper D20 (higher zooplankton standing stock) in the CEAS. This limitation of the mature habitat by the physical forcing and the seasonal reversal of the currents limits the spawning regimes of these fish because the carnivorous (planktivorous) fish like the Bombay Duck (oil sardine) can spawn only in those regions from where they can make it to their mature habitat in the NEAS (SEAS).